2022
DOI: 10.24815/siele.v9i1.21035
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers’ perception on the implementation of approaches to teaching literature in EFL classrooms

Abstract: The selection of appropriate approach(es) to teaching literature in EFL classrooms becomes a necessity that they can result in good performance of the students, both in their critical thinking aspect and their language proficiency. The problem appears when the lecturer does not implement a suitable approach to literary analysis when teaching literature to the EFL students. These problems led to the student’s inability to perform as expected. The present study examines how lecturers perceive the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…This is consistent with the findings of Shelton-Strong's study (2012), which claims that authentic reading materials push pupils to develop their own language skills. According to Febriani et al, (2022), choosing the right strategy (or approaches) to teaching literature in EFL classrooms is essential for students to do well in both their critical thinking and language proficiency domains. Reading literature provides students with a number of benefits, such as enhancing reflective and intentional learning and introducing them to critical thinking and cultural awareness (Hamid et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of Shelton-Strong's study (2012), which claims that authentic reading materials push pupils to develop their own language skills. According to Febriani et al, (2022), choosing the right strategy (or approaches) to teaching literature in EFL classrooms is essential for students to do well in both their critical thinking and language proficiency domains. Reading literature provides students with a number of benefits, such as enhancing reflective and intentional learning and introducing them to critical thinking and cultural awareness (Hamid et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is the creativity at its purest. This creative way to rethink is relevant to the dynamic social phenomena which makes a variance in theoretical basis, ethical values, and/or concrete moral issues involved in teaching materials, which gives rise to many meaning options in literary teaching (Febriani et al, 2022;Muthmainnah et al, 2020).…”
Section: Findingmentioning
confidence: 99%
“…Sixteen articles were chosen to answer the RQ 1. And these ten studies by (Al Sabiri & Kaymakamoğlu, 2019;Atek et al, 2020;Bunga Febriani et al, 2022;Fauziah, 2016;Granath, 2017;Jabeen & Sarifa, 2022;Ling & Chen, 2016;Resueňo & Ian Bel Resueňo, 2019;Suliman et al, 2019;Wahyuni et al, 2021), revealed that there are six main approaches employed by teachers in teaching literature, which are the information-based approach, moral-philosophical approach, paraphrastic approach, language based approach, reader response approach, and stylistic approach. Subsequently, four studies by Benonguil & Barnido (2022); Hernández (2020); Moustafa & Naima (2022) and Yimwilai (2015) suggested other teaching methods such as the experimental group approach, communicative approach, affective responses approach, and focus group discussion.…”
Section: Approaches Employed By Teachersmentioning
confidence: 99%